'The feeling of not being entitled to something': fertility, pregnancy, and sexuality among women with systemic lupus erythematosus in South Africa. (3rd May 2020) - Phuti, A; Hodkinson, B; Tikly, M; Schneider, M
Abstract : Objective : Fertility, pregnancy, and the postpartum period can pose many challenges for patients with systemic lupus erythematosus (SLE) in sub-Saharan Africa. We explored the perceptions and experiences of South African women relating to fertility and pregnancy. Method : In-depth interviews were conducted with 25 consenting women with SLE. We explored their perceptions and experiences on conception, pregnancy, and sexuality. Data were analysed using Nvivo software. Results : Participants had a mean age of 30.9 years (range 22–45 years) and mean disease duration of 4.5 years (range 1–5 years). The majority were black Africans, and the remainder were of mixed racial ancestry. Unemployment, low educational level, and singlehood status were the most predominant sociodemographic features. Most participants had been pregnant and a few reported being sexually inactive. Participants described many negative pregnancy outcomes including lupus flares, miscarriages, premature deliveries, prolonged hospitalization, and unexpected caesarean sections. Conflicting medical advice on conception, together with conflicting personal, cultural, and societal pressures to procreate, resulted in emotional turmoil and pessimism. Participants frequently described intimacy problems, loss of libido, and infidelity by partners leading to sexually transmitted infections. Aesthetic and physical concerns were perceived as the main causes of infidelity. Most participants felt confined to these relationships as they were financially dependent on their partners, which added to their stress. Conclusion : A combination of patient-centred care focusing on safe, effective contraception and medication targeting remission state, constant counselling, consistent information, and a pregnancy managed jointly by an obstetrics and rheumatology team could achieve optimum results.